(3GdLhGgQ GdKejfI aj ePgH YGde GdeOjfIs - (3CHh eMeO YHO Gddg Hf eMeO Hf fLe Hf TGS GdeUQj (B( (3Hf fRGQ GdLPGej(B)(3,J (B610 (3g` s ((3Ydi Hf eMeO GdHjWGQ s)
(3ChdgG (B:s
(3gh YbO eYGhVI Ydi PGJ bhdg YbO CONd GdgHI hGdhUjI s
(3BNQgG (B:s
(3Nda ef Pdc MGTjI GdYdGeI GdHGfj hUdi Gddg Ydi oeMeO hYdi Bdg hUMHg hSde JSdjeG s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B613s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs